Embodied time: Time production in advanced Quadrato and Aikido practitioners. Issue 1 (2nd January 2019) - Ben‐Soussan, Tal Dotan; Glicksohn, Joseph; De Fano, Antonio; Mauro, Federica; Marson, Fabio; Modica, Manuela; Pesce, Caterina
Abstract: Over the last few years, several studies have investigated the possible effects of mindfulness meditation on time perception. Mindfulness meditation has been linked to both longer time production (TP) and increased bodily perception, and bodily processes are in turn thought to lie at the core of human time perception. Nevertheless, the connection between mindful movements (MMs; i.e., specific types of mind–body coordination‐demanding physical activity) and time perception has been ignored. Consequently, in the current study we examined the effect of MMs on TP. A mixed observational study design was adopted to investigate whether (1) the extensive practice of MMs is associated with longer TP and interlimb coordination efficiency, and (2) there is a relationship between these two variables. Thirty‐four healthy adults volunteered, including 11 Aikido and nine advanced Quadrato Motor Training (aQMT) practitioners, and 14 physically non‐active controls. Practitioners of aQMT had significantly longer produced durations in contrast to the Aikido and control groups. In addition, longer produced duration was associated with increased coordination efficiency. In conclusion, the current results are in line with previous studies linking embodied time and mindful meditation, and suggest the importance of incorporating movement meditation, especially in the context of time estimation and the self.